Oxford Research Encyclopedia of Criminology and Criminal Justice 2017
DOI: 10.1093/acrefore/9780190264079.013.267
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of White-Collar Crime

Abstract: As far back as the 19th century, statistics on reported crime have been relied upon as a means to understand and explain the nature and prevalence of crime (Friedrichs, 2007). Measurements of crime help us understand how much of it occurs on a yearly basis, where it occurs, and the costs to our society as a whole. Studying crime statistics also helps us understand the effectiveness of efforts to control it by tracking arrests and convictions. Analysts can tell whether it is increasing or decreasing relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The FBI provides the most commonly used standard for official crime statistics in the U.S. As such, we will focus on white collar crime data reported by the FBI to highlight the strengths and limitations of this particular type of data. The FBI does not offer a universal definition or dataset of white collar crime (Cliff & Wall‐Parker, 2017). However, the FBI's Uniform Crime Reporting (UCR) Program does capture data on financial crimes, including embezzlement, money laundering, intellectual property theft/piracy, and various types of fraud (FBI, 2024).…”
Section: Measuring White Collar Crimementioning
confidence: 99%
See 1 more Smart Citation
“…The FBI provides the most commonly used standard for official crime statistics in the U.S. As such, we will focus on white collar crime data reported by the FBI to highlight the strengths and limitations of this particular type of data. The FBI does not offer a universal definition or dataset of white collar crime (Cliff & Wall‐Parker, 2017). However, the FBI's Uniform Crime Reporting (UCR) Program does capture data on financial crimes, including embezzlement, money laundering, intellectual property theft/piracy, and various types of fraud (FBI, 2024).…”
Section: Measuring White Collar Crimementioning
confidence: 99%
“…To address this definitional dilemma, Cliff and Wall‐Parker (2017) have suggested that “perhaps the best way to conceptualize white‐collar offenders is on a continuum that considers all aspects of the crime itself, the perpetrator, the relationship to the victim, and the position the perpetrator occupied that made it possible to commit the offense (p. 5).” With that said, we do not endorse any particular definition or conceptual approach in the present paper. Instead, we—like Simpson (2013)—argue that these conceptual disagreements have, for the most part, been largely ineffectual.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of factors have had some bearing on this trend though the impact of any particular factor is contested (Tonry, 2014). The lack of consensus may be explained to some extent by the absence of a comprehensive database detailing white-collar crime and arrest rates (Cliff and Wall-Parker, 2017). The Federal Bureau of Investigation’s Uniform Crime Reports record arrests for a small subset of white-collar crimes like fraud and the 1996–2005 reports indicate that, while the arrest rate for all crimes fell by 4.4%, the arrest rate for fraud fell by 24.2%.…”
Section: Conceptualising Prosecutorial Decision-making: An Ecological Modelmentioning
confidence: 99%
“…Quantitative information about the number and frequency of violations and prevention measures is scarce and often problematic. For instance, official statistics mirror enforcement capacities and priorities, not necessarily its success (see van de Bunt and Huisman 2007;Gibbs and Simpson 2009;Walburg 2015;Benson, Kennedy, and Logan 2016;and Cliff and Wall-Parker 2017 for an overview of measurement problems). In addition, victimization surveys often have low response rates and have often been administered by consultancy and/or audit firms that have their own agenda and may not always distinguish between white-collar, corporate, organized, and occupational crime (Walburg 2015).…”
Section: Types and Sources Of Datamentioning
confidence: 99%